Torulene and torularhodin, protects human prostate stromal cells from hydrogen peroxide-induced oxidative stress damage through the regulation of Bcl-2/Bax mediated apoptosis. (1st February 2017) - Du, Chao; Guo, Yahui; Cheng, Yuliang; Han, Mei; Zhang, Weiguo; Qian, He
Abstract: The current study was designed to elucidate the cytoprotective effects and possible mechanisms of torulene and torularhodin on hydrogen peroxide (H2 O2 )-induced oxidative stress damage in human prostate stromal cells (WPMY-1). After treated with H2 O2, a notable decrease was appeared in cell viability, yet the decrease was attenuated when cells were pretreated with torulene and torularhodin (0.5–10 μM) as evaluated by WST-1 assay. Pretreatment with these two carotenoids significantly attenuated H2 O2 -induced apoptosis in WPMY-1 cells through the inhibition of intracellular reactive oxygen species (ROS) and malondialdehyde (MDA) overproduction, as well as the activation of the activities in catalase (CAT), superoxide dismutase (SOD), and glutathione peroxidase (GSH-Px). Finally, pretreatment of cells with carotenoids resulted in the regulation of the mRNA and protein expression of Bcl-2 and Bax in H2 O2 -exposed prostate stromal cells. The present results indicate that both torulene and torularhodin can protect human prostate stromal cells from oxidative stress damage via Bcl-2/Bax mediated apoptosis.